Padrões do desenvolvimento da antera em espécies de Microlicieae (Melastomataceae) - Lima, Jamile Fernandes (2013)
Melastomataceae is a family of pantropical distribution, with representatives recognized mainly by their acrodromally veined leaves, but also by long stamens and/or appendices in connective and usually falciform with poricidal anthers. However, the variations found in the wall of the anthers induce the need for research on a larger number of species, especially in Microlicieae, one of the most representative tribes of Melastomataceae in Brazil, with over 90% of its species from Cerrado. In this context, this paper presents a structural study of Microlicieae anthers addressing two aspects: the anther wall development of Chaetostoma, Lavoisiera, Microlicia, Rhynchanthera, Stenodon and Trembleya finding features that contribute to the delineation of these genera (Chapter 1) and the development of polysporangiate anthers in Microlicia (M. euphorbioides, M. fasciculata, M. helvola and M. graveolens) (Chapter 2). The initial development of the anther wall is similar in the studied species, differentiating from periclinal divisions of secondary external layers. These differences lead to two types of anther wall development: monocotyledonous in Stenodon suberosus and Trembleya phlogiformis, and basic in the other species. The latter is reported in Melastomataceae for the first time. During microsporogenesis, tetrasporangiate anther wall consists of uniseriate epidermis, endothecium with thickening primary, middle (s) layer (s) and glandular tapetum, differentiating itself mainly by the number of strata of the middle layers. The presence of thickened endothecium cells in all species and the large number of strata in the middle layer of Lavoisiera imbricata, L. mucorifera, Rhynchanthera dichotoma and S. suberosus may be related to the pollination process, acting as an additional support in anther. At anthesis, most species presents anther wall composed of epidermis and endothecium or epidermis, endothecium and middle layer; only M. tetrasticha presents anther wall with thickened cells from epidermis and endothecium. Regarding the development of the polysporangiate anthers in Microlicia, the parenchymal tissue divides transversely, as can be observed from the early stages of development. During the anther dehiscence, both the longitudinal and transverse septa degenerate, leaving only some idioblasts with druses, which seems to indicate that these septa are not directly related to the pollen development, as suggested by some authors. With the comparative results, we conclude that the anther structural features indicate that Microlicia is a taxa close to Trembleya than to Lavoisiera, which in turn share a great number of characteristics with Rhynchanthera, such as dimorphic stamens, elongated connective, anther wall development of basic type, thickened epidermal cells, persistent endothecium, thickened endothecium cells and druses in connective. In all studied species of Microlicieae, Stenodon is the most distinct taxon presenting in common with the other Melastomataceae representatives only the basic type of anther wall development, epidermal cells with primary thickenings, persistence of a middle layer and presence of druses.